Valuing services in trade : a toolkit for competitiveness diagnostics - Sáez, Sebastián (Trade and development series., 2014)
The Service Trade Competitiveness Diagnostic (STDC) Toolkit is part of a larger agenda of trade competitiveness work developed by the World Bank's International Trade Unit in recent years. Services are a key input in countries' trade competitiveness, as well as a new source of trade diversification, making it critical to understand what factors and main constraints matter most for services competitiveness. The Toolkit provides a framework, guidelines, and set of practical tools to conduct a thorough analysis and diagnostic of trade competitiveness in the services sector with a methodology that.